Which factors influence the transition towards a healthy and sustainable food environment in Dutch hospitals? A qualitative view from stakeholders - Joline J. Wierda; Femke van Nassau; Sanne K. Djojosoeparto; Maartje P. Poelman (BMC Medicine)
Abstract Background Hospitals fulfill an important exemplary role in promoting health and well-being. It is therefore crucial to have a supportive food environment that stimulates healthy and sustainable food choices of patients, staff, and visitors. This qualitative study aimed to identify factors influencing the implementation of long-lasting actions to enhance the healthiness and sustainability of the food environment in the hospital setting in the Netherlands, from the perspective of different stakeholders. Methods Semi-structured interviews were conducted in hospitals realizing a healthy and sustainable food environment. Verbatim transcripts were thematically analyzed, guided by the Consolidated Framework for Implementation Research. Data were organized and interpreted per theme as well as stakeholder group. Results In three hospitals, 29 semi-structured interviews were conducted with 30 stakeholders from a wide spectrum of stakeholder groups (i.e., facility professionals, healthcare professionals, project coordinators, and board of directors). Identified themes and subthemes were: 1 the outer setting, with momentum for change, government-established policies and guidelines, collaboration and networks outside the hospital, and caterers’ and suppliers’ food offerings, interests, and contracts; 2 the innovation domain, with familiarity and compliance with the TEH program; 3 support at all levels, achieving organizational buy-in with communication as a strategy, and end user interests; 4 the inner setting, with key priority in policy and having a vision, available resources, infrastructure within the hospital, ambassadors, and gradual process with continuous effort; and 5 the individual domain with personal drive. Conclusions The results revealed an interplay of perceived factors that influence the enhancement of a healthy and sustainable food environment and underscored the importance of addressing various facilitators and barriers across multiple domains within and outside the hospital setting. To ensure successful integration of a healthy and sustainable food environment in hospitals, throughout the entire organization it is crucial to engage diverse stakeholders at all levels and address their barriers with tailored implementation strategies. We suggest verification of our findings in more hospitals.